2009
DOI: 10.1007/s00586-009-0968-y
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between the cervical spinal canal diameter and the pathological changes in the cervical spine

Abstract: A congenitally narrow cervical spinal canal has been established as an important risk factor for the development of cervical spondylotic myelopathy. However, few reports have described the mechanism underlying this risk. In this study, we investigate the relationship between cervical spinal canal narrowing and pathological changes in the cervical spine using positional magnetic resonance imaging (MRI). Two hundred and ninety-five symptomatic patients underwent cervical MRI in the weight-bearing position with d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
87
2
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 137 publications
(97 citation statements)
references
References 20 publications
4
87
2
1
Order By: Relevance
“…To better understand the development of ASD after anterior cervical arthrodesis and the overall prevalence of this problem, we focused our attention on the size of the cervical spinal canal and determined whether preoperative congenital stenosis predicted ASD at a minimum follow-up of 6 years. Morishita et al [31] found that a congenitally narrow canal had different effects on cervical kinematics. In other words, subjects with a congenitally narrow cervical canal may be exposed to a large mechanical loading at the cervical spine.…”
Section: Discussionmentioning
confidence: 99%
“…To better understand the development of ASD after anterior cervical arthrodesis and the overall prevalence of this problem, we focused our attention on the size of the cervical spinal canal and determined whether preoperative congenital stenosis predicted ASD at a minimum follow-up of 6 years. Morishita et al [31] found that a congenitally narrow canal had different effects on cervical kinematics. In other words, subjects with a congenitally narrow cervical canal may be exposed to a large mechanical loading at the cervical spine.…”
Section: Discussionmentioning
confidence: 99%
“…We defined the sagittal diameter of the CSF column at a given pedicle level as the sagittal cervical canal diameter [10][11][12][13]. The sagittal diameter of the spinal cord is nearly constant in adults, averaging approximately 8 mm from C3 to C7 [14].…”
Section: Measurement Of Sagittal Diameter Of Csf Columnmentioning
confidence: 99%
“…Unique pathologic and kinematic traits may exist in the patient with a developmentally narrow canal. Dynamic MRI studies have shown that patients with a congenitally narrow cervical canal (<13 mm) have increased segmental mobility in the cervical spine which may in turn predispose to the development of radiographic dynamic cord compression and potentially clinical myelopathy [36].…”
Section: Introductionmentioning
confidence: 99%